GASTRONOMIC TOURISM DEVELOPMENT IN GORONTALO PROVINCE - Yumanraya Noho; Dahlia Husain; Rosma Kadir (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
The tourism sector, shopping and culinary tours are part of cultural tourism activities that contributes around 45% of all cultural tourism activities. Gastronomic tourism is defined as the pursuit of eating and drinking experience that is unique and easy to remember. Gorontalo Province has considerable number of potential for gastronomic tourism yet stumbled upon several problems such as human resource, level of education and lack of mentoring in the community. The result of this literary research propose some solutions for those problems including, 1) food mapping, 2) organizing food related events, 3)gastrodiplomacy, 4) physical facilities, and 5) increasing awareness for mastering foreign language. Keyword: Tourism, Development, Gastronomy, Gorontalo,